Virginity as dissidence? Reflexions on O Marido Virgem, by Alfredo Gallis - Valentim, Jorge Vicente [UNESP] (Univ Estadual Paulista-unesp, 2019)
Little acknowledged by literary criticism, Alfredo Gallis (1859-1910) was a prolific writer in the period between the 19th and 20th centuries, having published more than a dozen texts with an expressive readership both in Portugal and in Brazil. This essay intends to develop some reflections on the novel O marido virgem (1900), with a reading that emphasizes an avant-garde treatment of themes related to sexuality and gender, in a context where Naturalistic aesthetics, monarchical thinking and conservatism still remained in the most different areas of knowledge and behavior. To do so, I take as a starting point his approaches on virginity and its different performances in his fiction, and how they can be understood as forms of expression of dissidence in the scenario of the 19th and 20th centuries.
Keywords: Alfredo Gallis; Dissidences; Sexuality; Virginity